A short note on heavy cunjevoi growth observed on commercial scallops (Pecten fumatus). (3rd April 2019) - Przeslawski, Rachel
ABSTRACT: Commercial scallops ( Pecten fumatus ) were collected from Bass Strait, Australia from 41 dredge tows. Of these, four dredges undertaken in February 2016 at 46 m depth returned scallops that were covered by ascidians of the Pyura stolonifera species complex, commonly known as cunjevoi. There were no obvious signs of immediate ill health in the scallops, with meat being assessed as normal quality and all scallops requiring force to separate the shells. Ascidian-encrusted scallops were significantly smaller, and previous tows in the same location ten and eight months earlier returned far fewer scallops with clean shells and no signs of ascidians. This suggests that both both scallop and ascidian recruitment and growth occurred during the period between sampling events. Future research combining laboratory experiments and field observations is recommended to understand this relationship and its potential impacts on scallop populations.